Reputation of the Manager - Its Strategic Importance: an Attempt to Determine Evaluation Criteria - Gołata , Krzysztof (Studia Oeconomica Posnaniensia, 2014)
In the present-day economy, the position of a company is determined not only by its economic performance, but is also dependent on non-economic factors. They all make up the notion of reputation, which is becoming increasingly important. The debate about the reputation of a company also involves the reputation of its manager. The question arises as to what extent the criteria for assessing a company’s reputation can be used in the evaluation of its managers. Based on an analysis of the criteria used in the evaluation of a company’s reputation, an attempt was made to identify which of them can be helpful in assessing the reputation of managers. The article presents the concept of a theoretical approach which requires empirical verification. The merits of the proposed criteria have been subjected to a preliminary assessment. Further work will aim at performing a thorough empirical analysis.